Application of Foot Massage for Hypervolemia with Leg Edema in Patients with Congestive Heart Failure in the ICCU - Putri Yuliana, Nely; Fadila, Erida; Syaripudin, Ahmad (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Heart failure is a complex syndrome that arises from conditions that impair the ventricles' ability to pump oxygen-rich blood, with common symptoms including dyspnea and edema. One complementary therapy for managing edema is foot massage. According to WHO data, the global prevalence of heart failure is 26 million cases. Meanwhile, West Java ranks fourth with a prevalence of 1.18% or 156,977 cases (Indonesian Health Survey, 2023). Method: A descriptive method was used with the application of case study results. Result: Foot massage was applied over three days, and changes were observed in the legs of patients with edema. Conclusion: It can be concluded that foot massage therapy is effective in reducing leg edema in patients with congestive heart failure because the massage promotes smoother lymphatic fluid flow, particularly from smaller lymphatic vessels to larger ones. This process is crucial because blocked or slowed lymphatic flow can reduce immune system effectiveness and disrupt bodily fluid balance.